Low polyethylene creep and wear following mobile-bearing unicompartmental knee replacement - Ghosh, P; Mohammad, HR; Martin, B; Campi, S; Murray, DW; Mellon, SJ (Springer, 2020)
Purpose: The Oxford unicompartmental knee replacement (UKR) has a fully congruent mobile bearing to minimise wear. However, with younger higher demand patients, wear remains a concern. The aim of this study was to quantify the wear rate of Phase 3 Oxford UKR bearings over the course of 5 years and to identify the factors that influence it.